Tax Design-Tax Evasion Relationship in Serbia: New Empirical Approach to Standard Theoretical Model - Randjelovic, Sasa (Industrija, 2015)
This paper provides evidence on the impact of the change in income tax rates and the degree of its progressivity on the scale of labour taxes evasion in Serbia, using the tax-benefit microsimulation model and econometric methods, on 2007 Living Standard Measurement Survey data. The empirical analysis is based on novel assumption that individual’s tax evasion decision depends on a change in disposable income, which is captured by the variation in their Effective Marginal Tax Rates (EMTR), rather than on a change in after-tax income. The results suggest that the elasticity of tax evasion to EMTR equals -0.3, confirming the Yitzhaki's theory, while the propensity to evade is decreasing in the level of wages and increasing in the level of self-employment income. The results also show that introduction of revenue-neutral, progressive taxation of labour income would lead to increase in labour tax evasion by 1 percentage point.
Keywords: Tax evasion; Tax reform; Dual income tax; Effective marginal tax rate